2011
DOI: 10.4103/0019-509x.92254
|View full text |Cite
|
Sign up to set email alerts
|

Is locally advanced breast cancer a neglected disease?

Abstract: LABC in the Indian scenario is an outcome of neglect due to patient and system factors. These factors offer an excellent opportunity to plan a community-oriented preventive strategy for the general population and practitioners to decrease the incidence of LABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…In the latter group there would be viable tumor cell nests outside the zone of post-NACT clinical tumor size. Although this study did not focus on the prognostic relationship among these findings, it is in consonance with other studies that have shown that the variety of pathologic responses *chi-square test; p < 0.05 significant **ANOVA one tailed; p < 0.05 significant seen indicates that the entire pre-chemotherapy tumor area should be removed [10,15]. For some authors, the diversity of pathologic findings indicates the need for mastectomy [16,17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the latter group there would be viable tumor cell nests outside the zone of post-NACT clinical tumor size. Although this study did not focus on the prognostic relationship among these findings, it is in consonance with other studies that have shown that the variety of pathologic responses *chi-square test; p < 0.05 significant **ANOVA one tailed; p < 0.05 significant seen indicates that the entire pre-chemotherapy tumor area should be removed [10,15]. For some authors, the diversity of pathologic findings indicates the need for mastectomy [16,17].…”
Section: Discussionsupporting
confidence: 82%
“…Locally advanced breast cancer (LABC) accounts for a large proportion of breast cancers in India; 40-60 % in some series. In these patients, breast conservation rates are poor [9,10]. OBS offers an attractive alternative in these cases to enable breast conservation.…”
Section: Introductionmentioning
confidence: 99%
“…This advanced presentation could be due to lack of awareness which in turn cause delay in getting surgical consultation or due to aggressive tumour biology. 10 The present study correlated receptor status of the malignancy with clinical and pathological parameters to assess this factor in Indian population. It was also observed in the present study that a majority (43.54%) of these patients were TNBC which are known to have aggressive tumour biology.…”
Section: Discussionmentioning
confidence: 97%
“…Lack of screening facilities and lack of infrastructure for early diagnosis is considered to be an important factor for the delay in diagnosis. Lower level of education and lack of awareness, wrong beliefs and initial treatment with traditional medicine, lower socioeconomic status and poor access to health care facility are other factors linked to the delay in diagnosis of the symptomatic disease in most of these developing countries like Pakistan (Igene 2008;Akhtar et al, 2011;Talpur et al, 2011;Khan et al, 2015). All these factors contribute to the time lag between appearance of symptoms in the patients and the time cancer is diagnosed and staged in the health care facility.…”
Section: Determinants Of Advanced Stage At Initial Diagnosis Of Breast Cancer In Pakistan: Adverse Tumor Biology Vs Delay In Diagnosismentioning
confidence: 99%